The effect of using fixed orthodontic appliances on periodontal health: Literature review: Efek penggunaan peranti ortodonti cekat terhadap kesehatan jaringan periodontal: Kajian pustaka - Eddy Heriyanto Habar; Wa Ode Nur Anisa (Makassar Dental Journal, 2022)
Fixed orthodontic is a appliance that is currently attracting the attention of many people and has been widely used by the wider community. The use of fixedorthodontic appliances can have both advantages and disadvantages effects on the periodontal tis-sue health. Factors that cause changes in periodontal tissue health in fixed orthodontic users are oral hygiene, toothbrushes, or-thodontic pressure and lack of ability from dentists. This article discusses the effect of usingfixed orthodontic appliances on the health of periodontal tissues. The use of fixed orthodontic appliances has a significant relationship to the health of periodontal tissues; have advantages effect in the form of decreasing the rate of periodontitis and also cause disadvantages effects in the form of inflammation of the gingiva.